"Compromises that we make": Whiteness in the dual language context. Issue 4 (2nd October 2017) - Burns, Meg
ABSTRACT: This case study of a two-way dual language school explores the role of whiteness in a bilingual space, specifically with regards to parent involvement. I ask how whiteness operates in this setting and how the school's response to parent involvement reflects and/or challenges white supremacy. Using the concept of interest convergence and additional concepts from whiteness studies, I argue that the focal school offers a unique example of administrators explicitly working against the domination of white parents by asserting the legitimacy of Mexican-American parents' cultural capital. However, structural factors, specifically lack of funding, created a context for white parents' continued influence. Additionally, I examine the variety of ways in which white parents explained their involvement, arguing that notions of "compromise" and "sacrifice" undermined their—and administrators—social justice orientations.